Chapter 3: Rootstock breeding: current practices and future technologies - Thompson, Andrew J.; Belen Pico, Maria; Yetişir, Halit; Cohen, Roni; Bebeli, Penelope J. (CAB eBooks, 2017)
This chapter explores how genetic diversity can be exploited more deeply to create new rootstock cultivars, and describes the current and future breeding strategies applicable to rootstocks. It considers how to combine different sources of genetic variation, for example by overcoming species barriers, and how to select useful rootstocks. The many traits that can be associated with the root system or conferred by a rootstock to the scion are outlined. The impact of the practice of grafting on breeding strategies is also discussed.
Vegetable grafting: principles and practices
Keywords: cultivars; genetic diversity; genetic variation; grafting; plant breeding methods; root systems; rootstock scion relationships; rootstocks; scions